Analysis of Digital Marketing Strategies in Increasing Sales of EM.ES Store in Pinrang Regency - Inayah Musrifa; Muh Tamrin; Bahtiar Herman (Edumaspul: Jurnal Pendidikan, 2025)
The fashion business in Indonesia has been developing rapidly. The main challenge for fashion entrepreneurs is not only to offer high-quality products but also to understand customer needs, utilize digital platforms, and optimize promotions to reach a wider market. The use of social media, influencer marketing, and customer loyalty programs are among the strategies widely implemented to increase sales.This study aims to identify marketing strategies that can enhance sales at EM.ES Store. The research employs a qualitative method. Data sources consist of observations, interviews, and documentation to understand marketing strategies and the factors influencing sales. The data analysis technique used in this study is analysis with the NVivo application, a qualitative data analysis software that assists in organizing, coding, and thematically analyzing interview data.